Pembelajaran Seni Tari Pada Anak Berkebutuhan Khusus Di SLB Negeri Prabumulih - Yessi Anggraini R; A. Heryanto; Nofroza Yelli (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2024)
This research aims to describe dance learning for children with special needs at the Prabumulih State Special School. The method in this research uses a qualitative descriptive method with triangulation data collection techniques from three data sources, namely interview observation and documentation. The results of this research show that dance learning at Prabumulih State Special School uses a therapeutic learning system using sign language in the form of codes or calculations from the teacher. Learning dance for children with special needs at Prabumulih State Special School can develop students' motor, sensory, communication and cognitive systems. This learning provides a platform for students with special needs to develop themselves so that they are useful in everyday life